Effects of sectorial productive concentration and spending on productivity in Loreto - Chong Ríos, Alexci Igor (2021)
The study evaluates the hypothesis that Loreto has a high productive concentration and this negatively impact production and that the execution of public spending as well as the concentration by sector have little effect on regional economic efficiency. The results find moderate productive concentration by economic sector as well as a negative impact of the concentration on production and a low impact on productivity. A 1% increase in spending translates on average 0.1575% to the increase in productivity. Loreto's participation in GDP is running by public sector spending, which explains the persistent penultimate position in the regional competitiveness index.